(untitled) (Physical Education, Health and Social Sciences, 2025)
Clinical laboratories in Punjab are critical to the healthcare system, contributing significantly to accurate diagnosis, treatment planning, and patient safety. This review explores the current regulatory framework governing clinical laboratories in Punjab, highlighting its evolution, challenges, and areas requiring reform. Despite the existence of national and provincial regulatory bodies such as the Punjab Healthcare Commission (PHC) and the Punjab Blood Transfusion Authority (PBTA), many laboratories especially in rural areas struggle with compliance due to infrastructural deficits, financial constraints, lack of trained personnel, and outdated practices. Key challenges include non-standardized laboratory practices, inadequate implementation of Quality Management Systems (QMS), and insufficient awareness of biosafety protocols. The role of stakeholders such as government agencies, professional bodies, clinicians, and laboratory staff is crucial in establishing a culture of compliance and continuous quality improvement. Emphasis is placed on the need for stakeholder engagement, strategic investment, ongoing training, and technology integration. Drawing from international models and best practices, the paper recommends strengthening licensing mechanisms, revising legal frameworks, and enhancing accreditation and surveillance systems to elevate laboratory services across Punjab. These improvements are essential for achieving high-quality, standardized, and safe laboratory diagnostics, ultimately improving healthcare outcomes in the region.